ANALISIS ANGGARAN PENDAPATAN BELANJA DAERAH KABUPATEN REMBANG TAHUN 2007 - Tahwin, Muhammad; Hastuti, Setyo (potensio, 2009)
The proportion of local revenue (PAD), Rembang againstbudget on average over three years from 2005 to 2007 waslow, amounting to 6.79%. Thus, Rembang dependence oncentral government is still very large which is reflected in theamount of fund balance averaged over the three years 2005-2007 amounted to 88.66%. In the year 2007 Apex districtbudget deficit, so we need alternative measures to reducethe level of deficit and dependence on the center include:policies to increase local revenue and spending policies aremore selective with based on performance.Keyword: Regional Shopping Revenue Budget,Rembang District